Neglect and Neurodevelopment: A Narrative Review Understanding the Link Between Child Neglect and Executive Function Deficits - Silvia Herrero-Roldán; Alexandra Martín-Rodríguez (Biomedicines, 2025)
Background: Childhood neglect is a pervasive yet often overlooked form of maltreatment that exerts profound and lasting effects on neurodevelopment. Unlike other types of abuse, neglect is characterized by the absence of essential stimuli and caregiving, which are critical for normal brain maturation, particularly in regions involved in executive function. Objective: This narrative review aims to critically explore the neurobiological mechanisms through which early-life neglect impairs the development of executive functions. Special emphasis is placed on alterations in brain structure and function, dysregulation of the hypothalamic–pituitary–adrenal (HPA) axis, and emerging epigenetic evidence. Methods: A comprehensive literature search (170 articles) was conducted across PubMed, Scopus, Web of Science, and PsycINFO, including studies published between 1 January 2000 to 31 March 2025. Relevant empirical and review articles were selected based on methodological rigor, relevance to executive functioning, and focus on child neglect. Results: Evidence reveals that neglect disrupts key neural circuits, particularly those involving the prefrontal cortex and amygdala, leading to deficits in attention, working memory, impulse control, and cognitive flexibility. Chronic stress associated with neglect also induces HPA axis dysregulation and elevated cortisol levels, which further compromise neural plasticity. Additionally, epigenetic modifications appear to mediate long-term cognitive and emotional consequences. Conclusions: Childhood neglect represents a distinct and critical risk factor for executive dysfunction. Understanding the neurodevelopmental consequences of neglect is essential for developing targeted prevention strategies and therapeutic interventions aimed at supporting cognitive resilience in affected populations.